Surface Energy Heterogeneity Profiles of Carbon Nanotubes with a Copolymer-Modified Surface Using Surface Energy Mapping by Inverse Gas Chromatography - Gerencsér Fruzsina; Rieder Norbert; Varga Csilla; Hancsók Jenő; Dallos András (Hungarian Journal of Industry and Chemistry, 2017)
The effectiveness and quantitative control of the surface transition of multi-walled carbon nanotubes (MWCNTs) was characterized by inverse gas chromatography (iGC). The surface energy profile of carbon nanotubes compatibilized with an olefin-maleic-anhydride-ester-amide (OMAEA)-type coupling agent was determined by a surface energy analyzer (SEA). The surface energetic heterogeneity with energy distributions of dispersive and specific (acid-base) components of the surface energy of the MWCNTs were determined at various surface coverages. The results of the surface energy mapping showed that surface treatment significantly reduced the dispersive surface energy of MWCNTs and increased the specific surface energy. Furthermore, the surface modification enhanced its Lewis basic character and simultaneously decreased the acidic character of MWCNTs. It has been demonstrated that the surface treatment modified the heterogeneity profiles of the energetic surface of the carbonaceous nanomaterials.